2020
DOI: 10.1186/s12968-020-0604-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of carotid atherosclerotic disease using three-dimensional cardiovascular magnetic resonance vessel wall imaging: comparison with digital subtraction angiography

Abstract: Background: A three-dimensional (3D) cardiovascular magnetic resonance (CMR) vessel wall imaging (VWI) technique based on 3D T1 weighted (T1w) Sampling Perfection with Application-optimized Contrast using different flip angle Evolutions (SPACE) has recently been used as a promising CMR imaging modality for evaluating extracranial and intra-cranial vessel walls. However, this technique is yet to be validated against the current diagnostic imaging standard. We therefore aimed to evaluate the diagnostic performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…High-resolution magnetic resonance (HR-MR) imaging has been recently introduced as a minimally invasive-advanced imaging technique for directly identifying the intracranial arterial wall (11,12), which may correlate with luminal angiography (13)(14)(15). In the recent years, some studies have shown the feasibility of HR-MR in the evaluation and characterization of intracranial atherosclerosis and steno-occlusive lesions (12,16,17). However, data on follow-up after EVT based on HR-MR are limited.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution magnetic resonance (HR-MR) imaging has been recently introduced as a minimally invasive-advanced imaging technique for directly identifying the intracranial arterial wall (11,12), which may correlate with luminal angiography (13)(14)(15). In the recent years, some studies have shown the feasibility of HR-MR in the evaluation and characterization of intracranial atherosclerosis and steno-occlusive lesions (12,16,17). However, data on follow-up after EVT based on HR-MR are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The suboptimal performance of DSA in detecting ulceration of symptomatic plaque has been previously reported (38)(39)(40). VW-MRI has high sensitivity, high specificity, and good agreement with DSA for detecting ulceration (29,31). In our study, the plaque ulcerations of some patients were validated by DSA and by histological examination after CEA.…”
Section: Discussionmentioning
confidence: 62%
“…The systematic differences in Max WT, Max VD, TVA, LA, and plaque volume might be due to the non-circular lumen shape, irregular shape of plaque, and different measurement habits in our study. Some systematic differences in diameter measurements, particularly for large-size vessel segments in other studies were noted (31). Nevertheless, these slight differences had no significant effect on the accuracy of diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…VWI for the diagnosis of CCAO has been reported to have high accuracy and sensitivity using DSA as a reference. 15,22,23 A few studies have focused on the signal intensity of the occluded segment of the CCAO. Previous studies have reported a higher prevalence of heterogeneous intensity at the beginning of the occluded segment and a 47.5% presence of high signal intensity in the occluded segment.…”
Section: Discussionmentioning
confidence: 99%